Nurses' knowledge and attitudes regarding pain management: Cross‐sectional survey in the Eastern Province of Saudi Arabia - Aminah Alsalman; Mansour Mansour; Fhaied Almobarak (Wiley, 2023)
Abstract Aim This study aims to investigate the nursing staff's knowledge and attitudes regarding pain management in the Eastern Province of Saudi Arabia. Design A quantitative descriptive cross‐sectional survey. Methods Between January and March of 2020, 183 registered nurses from two hospitals in the Eastern Province of Saudi Arabia completed the Nurses' Knowledge and Attitude Survey Regarding Pain. We determined the average mean score for both the individual and the aggregate scores and the t‐test. Results The nurses had an inadequate level of knowledge and attitudes regarding pain based on the average mean score for this factor. There was a statistically significant correlation between length of time spent working as a registered nurse and the nurses' reported scores on tests measuring their knowledge and attitude toward pain.